Inflammatory mediators in oral diseases: Pathogenic mechanisms - Cantiga-Silva, Cristiane [UNESP]; Faria, Flávio D. [UNESP]; Pinheiro, Tiago Novaes; Cintra, Luciano T.A. [UNESP] (My University, 2023)
The production of inflammatory mediators is triggered by inflammation inducers, which in turn alter the functionality of many tissues and organs. Bacteria present in the oral cavity can trigger an acute inflammatory response to induce gingivitis or pulpitis. Substances released by microorganisms such as lipopolysaccharides, antigens, and other virulence factors initiate an inflammatory and immune response, leading to host activation defense cells. Differently, oral inflammatory conditions such as oral lichen planus and submucosal fibrosis contain inflammatory mediators with the ability to induce the proliferation and invasion of cells genetically predisposed to cancerous lesions. As a result of cellular activation, inflammatory mediators, including cytokines, chemokines, arachidonic acid metabolites, and enzymes collectively contribute to tissue damage. This review is a compilation of recent studies on the role of inflammatory mediators in the pathogenesis of the most common diseases of the oral cavity.
Keywords: Immune response; Inflammatory mediators; Oral disease